Cytoplasmic overexpression of ALCAM is prognostic of disease progression in breast cancer. Issue 4 (16th February 2006) - Burkhardt, M; Mayordomo, E; Winzer, K-J; Fritzsche, F; Gansukh, T; Pahl, S; Weichert, W; Denkert, C; Guski, H; Dietel, M; Kristiansen, G
Abstract : Background: Activated leucocyte cell adhesion molecule (ALCAM, CD166) is a cell surface member of the immunoglobulin superfamily. ALCAM expression has prognostic relevance in prostate and colon cancer. Objective: To evaluate ALCAM protein expression in breast cancer by immunohistochemistry and to correlate expression levels with clinicopathological data. Methods: 162 primary breast carcinomas with a mean clinical follow up time of 53 months were immunostained using a monoclonal ALCAM antibody. The staining was evaluated as an immunoreactive score (IRS) and grouped into low v high for both membranous and cytoplasmic staining. Results: Intraductal and invasive carcinomas showed a higher ALCAM expression (median IRS 4 and 6 respectively) than normal breast tissue (IRS 2). In univariate survival analyses a significant association of high cytoplasmic ALCAM expression with shortened patient disease-free survival (mean (SD) five year non-progression rate, 69.4 (4.6)% v 49.4 (11.1)%, p = 0.0142) was found. In multivariate analyses of disease-free survival times, high cytoplasmic ALCAM expression (relative risk (RR) = 2.086, p = 0.026) and nodal status (RR = 2.246, p = 0.035) were significantly associated with earlier disease progression, whereas tumour grading (RR = 1.6, p = 0.052) was of borderline significance. Conclusions: The data suggest that strong cytoplasmic ALCAM expression in primary breast cancer, as detected by immunohistochemistry, might be a new marker for a more aggressive breast cancer biology.